2000
DOI: 10.1002/1521-3773(20001201)39:23<4324::aid-anie4324>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Bilayer Vesicles

Abstract: Nonionic amphiphilic cyclodextrins prepared by hydroxyethylation of heptakis(6‐alkylthio)‐β‐cyclodextrins form bilayer vesicles composed solely of amphiphilic cyclodextrins in water (see schematic representation). Such vesicles combine the properties of liposomes and macrocyclic host molecules, and create new possibilities for the development of advanced carrier and delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(147 citation statements)
references
References 22 publications
4
139
0
3
Order By: Relevance
“…The first bilayer vesicles composed of hydroxyethylated ␤-cyclodextrins ranged in size from 50 to 300 nm in water. 90 The vesicles were composed of bilayers of cyclodextrins that enclosed an aqueous interior. Recently, Ravoo's group 91 showed that a disulfide reducing agent, dithiothreitol, could break down the vesicles in water.…”
Section: Other Vesicle-forming Self-assembled Amphiphilic Systemsmentioning
confidence: 99%
“…The first bilayer vesicles composed of hydroxyethylated ␤-cyclodextrins ranged in size from 50 to 300 nm in water. 90 The vesicles were composed of bilayers of cyclodextrins that enclosed an aqueous interior. Recently, Ravoo's group 91 showed that a disulfide reducing agent, dithiothreitol, could break down the vesicles in water.…”
Section: Other Vesicle-forming Self-assembled Amphiphilic Systemsmentioning
confidence: 99%
“…The vesicles prepared by CD inclusion complexes have gained much attention due to their importance in enthusiastic natural biomembranes, [9,10] developing new biotechniques, smart materials, etc. [11] Reports are available on substituted CD bilayer vesicles [12] and b-CD substituted by carboxymethyl and amino groups on the narrow and wider sides, respectively, [13] to form supramolecular tapes which were 50À300 nm wide and up to 20 mm in length. The self-assembly of vesicles is based on the supramolecular complexation of guest-b-CD and guest in two-head inclusion model as well as one-head inclusion model.…”
Section: Introductionmentioning
confidence: 99%
“…Our model system is based on the multivalent inclusion binding of a coordination complex at the surface of ␤-cyclodextrin (␤CD) host vesicles. Previously we reported the preparation of amphiphilic ␣-, ␤-, and ␥-CDs and the corresponding bilayer vesicles, which have the ability to recognize and bind guests by size-selective inclusion in the CD host cavities at the vesicle surface (41)(42)(43)(44)(45). We also recently described the multivalent interaction of the Cu(II) and Ni(II) complexes of adamantyl (Ad)-functionalized ethylenediamine (en) L to a SAM of ␤CD molecules (46).…”
mentioning
confidence: 99%